2021
DOI: 10.3390/app11115099
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Quality under Different Soil Management Strategies: Combined Use of Statistical Approaches to Select the Most Informative Soil Physico-Chemical Indicators

Abstract: Assessment of soil quality under different management practices is crucial for sustainable agricultural production and natural resource use. In this study, different statistical methods (principal component analysis, PCA; stepwise discriminant analysis, SDA; partial least squares regression with VIP statistics, PLSR) were applied to identify the variables that most discriminated soil status under minimum tillage and no-tillage. Data collected in 2015 from a long-term field experiment on durum wheat (Triticum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
(100 reference statements)
3
10
0
Order By: Relevance
“…In general, relationships between BEST-derived variables and other measured variables met expectations because, for example, P MAC (or AC) increased as BD decreased [36]; in the same way, similar relationships were detected when relative field capacity was considered, as relatively higher RFC values highlight a reduced availability of soil air (and vice versa) [37]. However, regarding the accuracy of capacity-based soil indicators obtained by BEST, a further evaluation was carried out by comparing the summer data from this investigation (BD, P MAC , AC, RFC) with the corresponding measurements (i.e., from measured soil water retention curves) carried out in the same plots in spring 2015 (see data reported in Table 2 by Stellacci et al [37]). Starting from very similar BD values (differences within a factor 1.2 or 1.3 under NT or MT), the three remaining indicators showed, on average, relatively higher discrepancies under NT (a factor of 2.3) than MT (1.7), with the highest difference (overestimation by a factor of 4) for the air capacity under no-tillage.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In general, relationships between BEST-derived variables and other measured variables met expectations because, for example, P MAC (or AC) increased as BD decreased [36]; in the same way, similar relationships were detected when relative field capacity was considered, as relatively higher RFC values highlight a reduced availability of soil air (and vice versa) [37]. However, regarding the accuracy of capacity-based soil indicators obtained by BEST, a further evaluation was carried out by comparing the summer data from this investigation (BD, P MAC , AC, RFC) with the corresponding measurements (i.e., from measured soil water retention curves) carried out in the same plots in spring 2015 (see data reported in Table 2 by Stellacci et al [37]). Starting from very similar BD values (differences within a factor 1.2 or 1.3 under NT or MT), the three remaining indicators showed, on average, relatively higher discrepancies under NT (a factor of 2.3) than MT (1.7), with the highest difference (overestimation by a factor of 4) for the air capacity under no-tillage.…”
Section: Discussionsupporting
confidence: 60%
“…Many soil properties exhibit a two-stage response to soil management [17,40] and thus a complete understanding of the processes investigated requires that almost stable conditions are obtained. In this respect, the key role of long-term field experiments is well known and recognized [23,37,41]. In this study, as previously reported, the time elapsed from the last main soil tillage allowed for the study of relatively comparable soil conditions.…”
Section: Discussionsupporting
confidence: 55%
“…According to the procedure indicated by Reynolds et al [13], the pore volume distribution functions of the considered treatments were calculated. These waterretention-curve-derived indicators are widely used and suggested in the literature [30,31], also to verify plausible correlations with respect to independent variables (for example, K s ) and check the consistency of the results [32,33].…”
Section: Soil Physical Quality Determinationmentioning
confidence: 99%
“…Practically speaking, cultivated land fertility quality refers to the potential productivity determined by soil physicochemical properties and soil nutrient elements [63]. Cultivated land project quality can adjust the suitability of cultivated land through changing infrastructure and ancillary facilities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%